Sensation Seeking as a Moderator on the Relationship between School Climate and Bullying Behavior in Teenagers - Prawita, Egi; Febriani, Arum (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2021)
This study aimed at examining the role of sensation seeking as a moderator of school climate towards bullying. The research hypothesis is the sensation seeking has a role as a moderator in the relationship between school climate and the tendency to bullying. The participants were 230 middle school students. The data collection exerted the tendency to bullying scale, school climate scale, and sensation seeking scale. Who conducted moderation analysis by using macro-PROCESS analysis from Hayes. The result illustrated that sensation seeking has a role as a moderator in the relationship between school climate and the tendency to bullying. The discussion in this study focused on the importance of controlling sensation seeking to reduce the tendency to bullying by developing rational thinking and self-control and the importance of facilitating the thrill activities for adolescents with high sensation seeking.